Developing a Talent Management Model to Foster Product Innovation Through Marketing Strategy Integration - Mansur, Daduk Merdika (Golden Ratio of Mapping Idea and Literature Format, 2024)
This research aims to empirically examine the interplay between talent management, marketing strategy, and product innovation within organizations. Drawing on the foundational insights from recent studies, this research proposes that the strategic integration of talent management practices with marketing strategy processes is pivotal for fostering an environment conducive to product innovation. By employing a mixed-methods approach, the study seeks to validate propositions concerning the impact of innovation-focused constructs within marketing strategies, the role of knowledge transfer across product lifecycles, and the effectiveness of cross-functional teams in innovation projects. Additionally, the study will explore the mediating role of strategic integration in enhancing a firm's innovative performance. This research is expected to contribute to the theoretical and practical understanding of how organizations can leverage talent management and marketing strategy integration to achieve superior product innovation outcomes. This study seeks to illuminate the pathways through which organizations can synergize their talent and marketing strategies to not only navigate the complexities of modern markets but also to lead in innovation. By bridging the gaps identified in existing literature and providing empirical evidence on the proposed hypotheses, this research aims to offer actionable insights for businesses striving to enhance their competitive edge through integrated approaches to talent management, marketing, and innovation.